2020
DOI: 10.1007/s40200-020-00497-1
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and type 1 diabetes mellitus in children

Abstract: Objectives This study aimed to investigate the association between Helicobacter pylori infection with diabetes mellitus type one and the effect of infected Helicobacter pylori on glycemic control. Methods This case control study was conducted on children with and without type 1 diabetes mellitus (T1DM). Demographic data and gastrointestinal symptoms in both groups and glycemic control status and duration of diabetes were recorded in patients with T1DM. Stool test was done on all children to detect Helicobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Regarding lipids, a study showed that H. pylori infection can reduce the level of HDL and increase the levels of LDL and TG 51 . However, other studies have presented opposite findings 52,53 . Meta-analyses and prospective studies of large samples have shown that eradication of H. pylori infection has no significant effect on the levels of HDL, TG, or LDL 6,54 .…”
Section: Discussionmentioning
confidence: 92%
“…Regarding lipids, a study showed that H. pylori infection can reduce the level of HDL and increase the levels of LDL and TG 51 . However, other studies have presented opposite findings 52,53 . Meta-analyses and prospective studies of large samples have shown that eradication of H. pylori infection has no significant effect on the levels of HDL, TG, or LDL 6,54 .…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, this present meta-analysis found a positive association between T1DM and H. pylori infection, although it did not reach statistical significance. Another study revealed that H. pylori infection was not significantly associated with T1DM in children and that the glycemic control in these patients was similar between those who developed H. pylori infection and those who did not [34]. The potential association between H. pylori infection and T1DM remains a topic of debate, particularly in terms of glycemic control, gastrointestinal symptoms, infection prevalence, eradication and reinfection rates, and sanitary conditions [29].…”
Section: Discussionmentioning
confidence: 99%
“…This exclusion covered a range of factors, including 106 duplicate articles, 267 pieces with outcomes not directly pertinent to the investigation, as well as 66 articles categorized as reviews, letters, meta-analysis studies, and case reports. Following this rigorous culling, a meticulously curated set of 12 articles were selected and emerged as prime candidates for the study, as illustrated in Figure 1 [23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Characteristics and Methodologies Of The Included Studiesmentioning
confidence: 99%
“…Esmaeili et al ( 67 ), however, drew the opposite conclusion that H. pylori infection has no obvious connection with diabetes mellitus in children aged 5-15 years, and there is obvious difference in blood glucose control between T1DM patients who are H. pylori positive and those who are H. pylori negative. Results of a meta-analysis conducted by Dai et al suggested that H. pylori infection was positively correlated with HbA1c levels in T1DM adolescents and children ( 68 ).…”
Section: Helicobacter Pylori and Autoimmune Diseasesmentioning
confidence: 99%